Instability of Superoxide Dismutase 1 of Drosophila in Mutants Deficient for Its Cognate Copper Chaperone - Kirby, Kim (American Society for Biochemistry and Molecular Biology, 2008)
Copper,zinc superoxide dismutase (SOD1) in mammals is activated principally via a copper chaperone (CCS) and to a lesser degree by a CCS-independent pathway of unknown nature. In this study, we have characterized the requirement for CCS in activating SOD1 from Drosophila. A CCS-null mutant (Ccs(n)(29)(E)) of Drosophila was created and found to phenotypically resemble Drosophila SOD1-null mutants in terms of reduced adult life span, hypersensitivity to oxidative stress, and loss of cytosolic aconitase activity. However, the phenotypes of CCS-null flies were less severe, consistent with some CCS-independent activation of Drosophila SOD1 (dSOD1). Yet SOD1 activity was not detectable in Ccs(n)(29)(E) flies, due largely to a striking loss of SOD1 protein. In contrast, human SOD1 expressed in CCS-null flies is robustly active and rescues the deficits in adult life span and sensitivity to oxidative stress. The dependence of dSOD1 on CCS was also observed in a yeast expression system where the dSOD1 polypeptide exhibited unusual instability in CCS-null (ccs1Δ) yeast. The residual dSOD1 polypeptide in ccs1Δ yeast was nevertheless active, consistent with CCS-independent activation. Stability of dSOD1 in ccs1Δ cells was readily restored by expression of either yeast or Drosophila CCS, and this required copper insertion into the enzyme. The yeast expression system also revealed some species specificity for CCS. Yeast SOD1 exhibits preference for yeast CCS over Drosophila CCS, whereas dSOD1 is fully activated with either CCS molecule. Such variation in mechanisms of copper activation of SOD1 could reflect evolutionary responses to unique oxygen and/or copper environments faced by divergent species.